2006
DOI: 10.1161/01.hyp.0000196306.42418.0e
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and the Risk of Incident Hypertension in Men

Abstract: Abstract-Evidence suggests that hypertension may share a similar pathophysiology with cardiovascular disease (CVD).Thus, dyslipidemia, a strong predictor of CVD, may also predict incident hypertension. We analyzed 3110 men free of hypertension, CVD, and cancer from the Physicians' Health Study, who provided baseline blood samples from which we measured total cholesterol (TC) and HDL cholesterol (HDL-C), and calculated non-HDL-C and the TC/HDL-C ratio. We categorized each lipid parameter into quintiles and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
198
3
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(233 citation statements)
references
References 33 publications
23
198
3
9
Order By: Relevance
“…13 That aggregation of cardiometabolic risk factors for CHD 14 likely reflects the intricate underlying interactions by which dyslipidaemia anticipates both hypertension 15 and frank hyperglycaemia, 16 and in turn, higher BP predicts both glucose intolerance and diabetes. 3,17 Notably, lipid abnormalities, obesity and adverse cardiovascular risk profile were homogeneously distributed across the two 110-125 and 100-109 mg 100 ml À1 intervals in contrast with the attenuated prevalence of risk factors in the latter category emerging from previous cross-sectional analyses.…”
Section: Discussionmentioning
confidence: 99%
“…13 That aggregation of cardiometabolic risk factors for CHD 14 likely reflects the intricate underlying interactions by which dyslipidaemia anticipates both hypertension 15 and frank hyperglycaemia, 16 and in turn, higher BP predicts both glucose intolerance and diabetes. 3,17 Notably, lipid abnormalities, obesity and adverse cardiovascular risk profile were homogeneously distributed across the two 110-125 and 100-109 mg 100 ml À1 intervals in contrast with the attenuated prevalence of risk factors in the latter category emerging from previous cross-sectional analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This class of molecules is important physiologically for nutrition, energy, membrane integrity, cellular signaling, binding, and transport of important minerals and vitamins. However, excessive amounts of lipids or modification of these lipids (i.e., dyslipidemia) directly contribute to altered redox homeostasis, oxidative stress, and hypertension (105,241). Epidemiologic studies, such as the Helsinki Heart Study and Physician Health Study, demonstrate that higher levels of the LDL/HDL ratio (Ͼ4.4) and higher cholesterol levels are associated with rapidly deteriorating kidney function and hypertension, respectively (288).…”
Section: Fig 5 Schematic Showing the Link Between Cardiometabolic Smentioning
confidence: 99%
“…1 The clustering of multiple cardiovascular risk factors in individuals is common, [1][2][3][4] and it has been observed that the impact of concurrent risk factors on cardiovascular disease (CVD) is more than additive. 5,6 Dyslipidaemia is found in a high proportion of hypertensive patients, 4,[7][8][9][10][11] and the presence of both conditions results in a significant increase in the risk of CVD. 12,13 Recent clinical trials have demonstrated significant benefits of statin therapy on the occurrence and outcome of cardiovascular events in high-risk groups, including patients with a history of coronary heart disease (CHD), patients with type II diabetes and patients aged 70 years or more.…”
Section: Introductionmentioning
confidence: 99%